التعليم من أجل التفكير في مجال التربية والتعليم - هويدي, عبد الباسط ، (Sciences de l'Homme et de la Société, 2016)
أكد التربويون على أهمية التفكير ومهاراته في العملية التربوية مع استهداف الوصول إلى تلميذ مفكر جيد لا حافظ للمعارف فقط يمكنه التعامل مع مشكلات الحياة ومن ثَمَّ عمل القائمون على النظم التربوية على تضمين المناهج تعليم التلميذ مهارات وأنماط التفكير من خلال التعليم المباشر التفكير أو دمج تعليم التفكير مع المحتوى الدراسي أو التعليم من أجل التفكير وهذا الأخير يتم باستعمال أساليب عديدة من خلال عناصر كثيرة منها المحتوى الدراسي والمعلم والسياسات والأهداف التربوية وبيداغوجيات التدريس وطرائقه ومن خلال البيئة المدرسية والوسائل التعليمية والتقويم التربوي.   Abstract : Educators have focused on the importance of thinking and skills in the educational process and targeting of access to good and thinker student not kept knowledge only. Can deal with life's problems accordingly, interested in the educational systems cared include curricula how to teach the student the skills and patterns of thinking through the direct teaching of thinking or merging teaching thinking with the course content or education in order to think The latter is done by using several methods through many elements, including course content and the teacher and the educational policies and goals and Pedagogies teaching methods and through the school environment educational means and educational evaluation.